Flexible Livestock Grazing for Soil and Ecosystem Restoration - Louhaichi, Mounir; Gouhis, Fethi; Kailene, Jamel; Gamoun, Mouldi (CGIAR System Organization, 2024)
Restoring rangelands: the art of flexible livestock grazing to restore soil health, ecosystem function and ecosystem services.